Political conduct - Philp, Mark (Harvard University Press, 2007)
Philp explores how political processes and practices shape political values like liberty, justice, equality, and democracy. Mining the history of political episodes and political thinkers, including Caesar and Machiavelli, Philp argues that through political activity ""values are articulated and embraced, and they become powerful motivating forces.""